2021
DOI: 10.14309/ajg.0000000000001225
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal Epidermoid Metaplasia: Clinical Characteristics and Risk of Esophageal Squamous Neoplasia

Abstract: INTRODUCTION: Esophageal epidermoid metaplasia (EEM) is a rare disease. METHODS: Patients with EEM diagnosed between 2014 and 2020 were reviewed. RESULTS: Forty EEM cases were identified. EEM occurred in 9 (23%) patients before, concordant, or after esophageal squamous cell carcinoma (ESCC). EEM was associated with previous esophageal lichen planus in 5 patients, Barrett's esophagus 7, and esophageal adenoca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 14 publications
(22 reference statements)
0
11
0
Order By: Relevance
“…Esophageal leukoplakia is often detected in close proximity to high-grade squamous cell dysplasia and squamous cell carcinoma suggesting it to be a preneoplastic lesion [ 1 ]. In a case series by Kamboj et al with 40 patients with EEM 25% of the patients were found to have squamous cell neoplasia before, synchronous to, or after epidermoid metaplasia of the esophagus [ 8 ]. Singhi et al reported a case series with 18 patients with esophageal leukoplakia amongst which 17% had high-grade dysplasia or even squamous cell carcinoma [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Esophageal leukoplakia is often detected in close proximity to high-grade squamous cell dysplasia and squamous cell carcinoma suggesting it to be a preneoplastic lesion [ 1 ]. In a case series by Kamboj et al with 40 patients with EEM 25% of the patients were found to have squamous cell neoplasia before, synchronous to, or after epidermoid metaplasia of the esophagus [ 8 ]. Singhi et al reported a case series with 18 patients with esophageal leukoplakia amongst which 17% had high-grade dysplasia or even squamous cell carcinoma [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…No guidelines exist for the ideal frequency and pattern for evaluation or surveillance of esophageal leukoplakia [ 10 ]. Given concern for preneoplastic potential and its association with squamous cell dysplasia and esophageal cancer, the need for close surveillance or endoscopic interventions has been suggested [ 1 , 8 ]. Endoscopic resections for small dysplastic lesions and ablation therapy for large dysplastic lesions have been proposed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heavy smoking and alcohol intake are proposed risk factors, although the aetiology remains uncertain 2 3. Epidermoid metaplasia is associated with synchronous or metachronous squamous neoplasia and premalignant conditions, such as lichen planus and Barrett’s oesophagus 4. The presence of multiple mutations, including TP53, in epidermoid metaplasia corroborates its malignant potential 5.…”
Section: Answermentioning
confidence: 96%
“…2d). 20,21 Kamboj et al identified that 25% (10 of 40) of patients with an EEM diagnosis had squamous neoplasia diagnosed (before, at, or after EEM diagnosis). 20 Cottreau et al also reported an increased prevalence of EEM in patients with squamous neoplasms.…”
Section: Conventional Well-differentiated Squamous Cell Carcinomamentioning
confidence: 99%